2022
DOI: 10.1002/adpr.202100354
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet/Visible Quasicylindrical Waves on Semimetal Cd3As2 Nanoplates

Abstract: Resolving the photonic modes in real space is essential to understand the fundamental process and control of photonic behavior in optoelectric devices. However, the understanding of the photonic modes of semimetal Cd3As2 is still lacking. Herein, the quasicylindrical waves (QCW) on Cd3As2 nanoplates using photoemission electron microscopy (PEEM) are found out. The QCW is due to the optical field scattered by subwavelength indentations, with wavelength being the same as the incident light, and their amplitude d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It was found that QCW is of the same wavelength as the input light and decays at a rate of r1/2 from the scattering source. Transverse magnetic modes were found to dominate the QCW pattern, depending on the excitation polarization relative to the Cd3As2 nanoplate edges 164 . Additionally, numerical simulations indicated that the Cd3As2 metasurface may improve absorption when compared with naked nanoplates.…”
Section: Photonics With 3d Dsm Cd3as2mentioning
confidence: 93%
See 3 more Smart Citations
“…It was found that QCW is of the same wavelength as the input light and decays at a rate of r1/2 from the scattering source. Transverse magnetic modes were found to dominate the QCW pattern, depending on the excitation polarization relative to the Cd3As2 nanoplate edges 164 . Additionally, numerical simulations indicated that the Cd3As2 metasurface may improve absorption when compared with naked nanoplates.…”
Section: Photonics With 3d Dsm Cd3as2mentioning
confidence: 93%
“… 163 The QCW is an optical field scattered by subwavelength indentations, distributed along a surface over several wavelengths, containing both radiative and evanescent components. The optical QCW on Cd3As2 nanoplates has recently been studied 164 by a team of researchers across a wide range of wavelengths from ultraviolet (UV) to visible. It was found that QCW is of the same wavelength as the input light and decays at a rate of r1/2 from the scattering source.…”
Section: Photonics With 3d Dsm Cd3as2mentioning
confidence: 99%
See 2 more Smart Citations
“…This frequency shift signifies the instantaneous photogeneration of free carriers in the laser field . These observations suggest that Cd 3 As 2 possesses a metal-like transient response similar to graphene, making it suitable as a high-speed device and surface plasmon–polariton (SPP) carrier . The harmonic intensity as a function of the laser power is depicted in Figure d, revealing a clear division into two distinct regions at 0.17 TW/cm 2 .…”
mentioning
confidence: 86%